Potential Effects of Global Warming on Quail Populations - Fred S. Guthery; N. David Forrester; Kenneth R. Nolte; Will E. Cohen; William P. Kuvlesky Jr. (National Quail Symposium Proceedings, 2017)
Populations of scaled quail (Callipepla squamata) and northern bobwhites (Colinus virginianus) have declined in North America coincident with global warming. We speculate on a cause-effect relation between global warming and quail declines. Quail are sensitive to operative temperatures >38.7 C, which commonly occur under natural conditions in southern latitudes. Based on empirical results, the laying season for quail may be reduced by as much as 60 days because of high temperatures. We provide mechanistic models that show how reduction in length of the laying season suppresses per-capita annual production. Global warming could be associated with declining quail populations through suppression of reproduction; it also could exacerbate the effects of habitat loss and fragmentation. These possibilities should be explored in field and laboratory research.